1993
DOI: 10.1143/jjap.32.1712
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rare Earth Ions on BaO-TiO2-Rare Earth Oxide Ceramics for Microwave Applications

Abstract: The dielectric ceramic materials, 0.143BaO-0.714TiO2-0.143 rare earth oxides (REO x ), have unique dielectric properties at microwave frequencies, which depend on the rare earth element (RE=Pr, Nd, Sm). In order to study the effect of the rare earth ions on dielectric properties, infrared reflection spectra of these ceramics were measured from 50 to 4000 cm-1 at room temperature. These data were analyzed according to the model proposed by Gervais and Piriou. Also, the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Several authors studied [3,5,10,11,13,16,19,21,29,41,57,56,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] the dielectric properties of Ba 6-3x Ln 8 þ 2x Ti 18 O 54 ceramics for different values of x and Ln = La, Pr, Sm, Nd, Eu, Gd and are given in Table 5.3. A study of Table 5.3 shows that the ceramics based on Eu, Sm and Nd have high quality factors (Qf) up to 14 000 GHz.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors studied [3,5,10,11,13,16,19,21,29,41,57,56,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] the dielectric properties of Ba 6-3x Ln 8 þ 2x Ti 18 O 54 ceramics for different values of x and Ln = La, Pr, Sm, Nd, Eu, Gd and are given in Table 5.3. A study of Table 5.3 shows that the ceramics based on Eu, Sm and Nd have high quality factors (Qf) up to 14 000 GHz.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…Figure 5.1 shows the phase diagram for the ternary BaO-RE 2 O 3 -TiO 2 system. Kolar et al [4], Polyakov et al [9] and Fukuda et al [10] all assigned the 1:1:5 compound for BaNd 2 Ti 5 O 14 with orthorhombic lattice parameters practically coinciding with those of Gens et al [7] for the 1:1:4 [BaNd 2 Ti 4 O 12 ], a stoichiometry first suggested by Razgon et al [6]. In 1986, Jaakola et al [11] reported that the true stoichiometry for the 1:1:4 and 1:1:5 phase must be closer to 15:19:72 (Ba 3.75 Nd 9.5 Ti 18 O 54 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…% Ba4.05Pr9.3Ti 18 6.9 vol. Based on the results of XRD, XMA, and, the dielectric properties of Bae-xPrs+MTiisC^ system, it was suggested that BaPr 2 Ti 5 0i 4 ceramics are composed of mixed phases, approximately, 85.0 vol.…”
Section: Discussionmentioning
confidence: 99%